Post-varicella vaccination uveitis in a child with nephrotic syndrome receiving immunosuppressive treatment: a case report - Andrade, Catarina; de Almeida Cordeiro, Miguel; Baeta Baptista, Rute; Sousa Nunes, Beatriz; Garcia, Ana Margarida; Milheiro Silva, Tiago; Valente Pinto, Marta (Frontiers in Pediatrics, 2025)
Patients with nephrotic syndrome are at heightened risk of infections due to the underlying disease pathophysiology and the effects of immunosuppressive therapies. Varicella-zoster virus (VZV) infection can cause severe complications in immunocompromised individuals. Concerns about the safety of live attenuated vaccines in this population persist. Emerging vaccination strategies incorporate pre-vaccination risk stratification algorithms based on immunological criteria. We present a case of a five-year-old male with corticosteroid-dependent nephrotic syndrome, in complete remission on mycophenolate mofetil therapy, who received the varicella vaccine after meeting immunocompetence criteria. Fourteen days post-vaccination, he developed scant vesicular lesions, with VZV DNA detected by PCR via swab. By day 16 post-vaccination, he presented with left-eye panuveitis. VZV DNA was also detected in the blood by PCR. Differentiation of VZV vaccine strains from wild-type strains was not possible. Additionally, molecular testing for VZV in the aqueous humor was not performed. However, given the temporal association with varicella vaccination, the detection of VZV in the blood and cutaneous lesions, and most importantly, the immunosuppression of the patient, post-vaccination ocular varicella was assumed even without an epidemiological history of varicella exposure. This case highlights the importance of a thorough immunocompetence assessment before administering live vaccines to immunosuppressed patients, as well as close post-vaccine monitoring and a high index of suspicion for complications to optimize vaccine safety in this vulnerable group. Patients with nephrotic syndrome require vaccination strategies tailored to their individual risk.